Design of Reverse Vending Machine Body and Storage System - Lokman, Muhammad Izzad Aqil; Abd Rahim, Abd Khalil (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Recycling behavior among civil society is unsatisfactory. It is because lack of center waste management that can also source be the reason that general public does not want to recycle in Malaysia. Research have been done to collect data of Reverse Vending Machine can be center waste of management. Reverse vending machine are popular at overseas to maintaining the behavior of recycling. To overcome this problem, Reverse vending machine have been designed to become center waste management in Malaysia. This project used George E Dieter design process to design this machine. The design process consists of eight phase which are Define problem, Gather information, Concept generation, Concept evaluation, Product architecture, Configuration design, Parametric design and Detail Design. The existing patent and available machine were referred to generate idea for reverse vending machine body and storage system. The selected idea and concept are used to modelled using Solidwork Software. Calculation and analysis also have been done to get the result of system. Based on analysis and calculation, the result of product can store about up to 15,000 sheets of paper, 2,488 bottle shredded, 6000 can shredded and 238 glass. The overall dimension of product 1690mm x 1250mm x 1800mm.